Long-term impact of pneumococcal conjugate vaccines for children on adult pneumococcal pneumonia in Japan: Two multicenter observational studies from 2011 to 2020. Issue 37 (2nd September 2022) - Maeda, Haruka; Gopal Dhoubhadel, Bhim; Sando, Eiichiro; Suzuki, Motoi; Furumoto, Akitsugu; Asoh, Norichika; Yaegashi, Makito; Aoshima, Masahiro; Ishida, Masayuki; Hamaguchi, Sugihiro; Otsuka, Yoshihito; Morimoto, Konosuke
Highlights: Serotypes of adult pneumococcal CAP in 2011–2020 in Japan were evaluated. Serotype distribution pre and post introduction of PCVs for children were assessed. The proportion of PCV13 serotypes decreased after PCV13 introduction for children. There has been no decrease in the proportion of PCV13 serotypes since 2017. Abstract: Background: Pediatric pneumococcal conjugate vaccines (PCVs) introduction has directly and indirectly reduced pneumococcal pneumonia and invasive disease caused by PCV-covered serotypes among children and adults globally. In Japan, both PCV7 and PCV13 were introduced into the national immunization program (NIP) for children in 2013. However, the long-term impact of PCV use in children on adult pneumococcal pneumonia in Japan remains unclear. Methods: We assessed serotypes isolated from adult pneumococcal pneumonia patients (in- and outpatients) in two multicenter observational studies in Japan: 2011–2014 and 2016–2020. The latter study period was divided into two periods to evaluate changes after PCV introduction in children. The Quellung reaction was used to determine serotypes. We evaluated trends of individual and vaccine-covered serotypes over three periods and assessed the difference in changes by patient group before and after the introduction of pediatric PCVs. Results: A total of 650 patients were enrolled: 224, 322, and 104 in 2011–2014, 2016–2017, and 2018–2020, respectively. The median age was 73 years; 59.7% (388/650) were male; 86.9% (565/650) had comorbidities; and 10.2% (66/650) were nursing-home residents. The proportion of PCV13 serotypes decreased from 52.7% in 2011–2014 to 30.4% in 2016–2017 (p <0.001) after PCV13 introduction for children. However, PCV13, PCV15, and PCV20 serotypes still accounted for 38.5, 43.3, and 59.6% of total pneumococcal pneumonia in 2018–2020, respectively. Decline of PCV13 serotypes was more marked in patients aged ≥65 (-23.5%; p <0.001) than those aged <65 (-12.3%; p = 0.104) from 2011–2014 to 2016–2020. The proportion of PPSV23 non-PCV13 serotypes didn't change over time. Conclusions: The proportion of adult pneumococcal pneumonia caused by PCV13 serotypes in Japan declined after pediatric PCVs introduction into NIP, possibly due to indirect effects of pediatric PCVs. However, use of new PCVs in Japanese adults may potentially prevent additional pneumococcal pneumonia cases. Now, pneumococcal vaccination strategy for older adults requires discussion.